Ischemic Preconditioning Enhances Performance and Erythrocyte Deformability of Responders - Tomschi, Fabian; Niemann, David; Bloch, Wilhelm; Predel, Hans-Georg; Grau, Marijke (International Journal of Sports Medicine, 2018)
This pilot study aimed to evaluate the differential effects of a remote ischemic preconditioning (rIPC) manoeuvre on performance and red blood cell (RBC) deformability compared to a sham control and a placebo setting. Ten male subjects performed three test settings in a single-blind, crossover, and randomized control design. All settings started with 20 min of rest and were followed by 4 cycles of occlusion/reperfusion consisting of 5 min each. During rIPC and placebo, the cuff pressure was inflated to 200 mmHg and 120 mmHg, respectively. During the sham control setting, 10 mmHg pressure was applied. All tests were followed by a cycle exercise with lactate diagnostics. Power at 2 and 4 mmol/l lactate thresholds were calculated. RBC deformability was measured before and after the respective manoeuvre. Results showed that no effect resulted from any manoeuvre on performance values or RBC deformability. But 6 subjects showed a higher power at the 2 mmol/l threshold, and 5 subjects exerted higher power at the 4 mmol/l threshold when the rIPC manoeuvre preceded the exercise. In these responsive subjects, RBC deformability also improved. Hence, rIPC effects are much influenced by the subjects’ responsiveness, and improved RBC deformability might contribute to enhanced performance in responsive subjects.
Keywords: remote ischemic preconditioning; red blood cells; performance; lactate; deformability; cycling